Experiential Marketing: The New Paradigm - Shukla, Timira (Indian Journal of Marketing, 2007)
All organizations everywhere, exist to create and deliver value to their customers. Building, designing and offering holistic experience to the customer is also a value proposition, which can enable organization in developing sustainable competitive advantage. Experiential Marketing focuses on customer experiences that evoke the senses (sight, smell, sound, touch&taste), heart and the mind. The new paradigm is a shift from Traditional Marketing, which focuses on features (characteristics that supplement the product) and benefits (performances characteristics that customers seek from a product). The article describes how to evoke customer emotions deep - seated in the mind and create a connection with the heart.